Multisite rTMS combined with cognitive training modulates effective connectivity in patients with Alzheimer's disease - Qin, Yuanyuan; Ba, Li; Zhang, Fengxia; Jian, Si; Tian, Tian; Zhang, Min; Zhu, Wenzhen (Frontiers in Neural Circuits, 2023)
Purpose To investigate the effective connectivity (EC) changes after multi-site repetitive transcranial magnetic stimulation (rTMS) combined with cognitive training (COG). Method 10Hz rTMS over left dorsal lateral prefrontal cortex (DLPFC) and lateral temporal lobe (LTL) were delivered for 4 weeks combined with COG. AD patients were divided into real (real rTMS+COG, n=11) or sham (sham rTMS+COG, n=8) group to underwent neuropsychological assessment, resting-state fMRI and 3D brain structural imaging before (T0), immediately at the end of (T4), and 4 weeks after treatment (T8). A 2×3 factorial design with “time” as within-subject factor (3 levels: T0, T4, T8) and “group” as between-subject factor (2 levels) were used to investigate the EC changes related to stimulation targets on the rest of brain, as well as the causal interactions among 7 resting state networks based on granger causality analysis (GCA). Results At voxel-level, the EC changes from left DLPFC out to left inferior parietal lobe and left superior frontal gyrus, as well as from left LTL out to left orbital frontal cortex had significant group × time interaction effect. At network level, significant interaction effect has been identified on the EC increment from limbic network out to default mode network. The EC decrease at voxel level and EC increase at network level were all associated with better functioning in the ability of daily living and cognition. Conclusions Multi-site rTMS combined with cognitive training could modulate effective connectivity in patients with AD, doing better for the ability of daily living and cognitive function.